Existing condition analysis of mangrove community structure at Bolihutuo Coast Area, Boalemo, Gorontalo Province - Moha, Yowan; Bay, Maria Kriscintya Ani; Sentia, Sentia; Kasim, Faizal (Universitas Malikussaleh, 2022)
The current study aimed to determine the existing condition of the extent and ecological developmental of the mangrove forest area at one coast located on the Tomini Bay, precisely, at the Bolihutuo Village coast Boalemo District, Gorontalo province. The data were collected for two months from August to September 2021, consisting of the mangrove extent area digitized from Google earth and the mangrove biophysical sampling using line-transect plots in different sizes 10x10 and m 5x5 m to examine categories mangrove levels of tree and saplings. The result showed that mangrove patches sized between 0.08 - 29.35 ha, which constructed a total area of 60.61 ha of mangrove forest in Bolihutuo. A total of 10 mangrove species were found as the occupant of the forest area where the dominant species was found in Rhizophora stylosa at the tree and sapling levels. The co-dominance was found different at both levels, namely Ceriops decandra at the sapling level while Rhizophora mucronata species at the tree level.Keywords: Mangrove patch; Dominant rank; IVI; Species richness; R. stylosa